Entrepreneurship, innovation, and platforms - Furman, Jeffrey L.; Gawer, Annabelle, 1969-; Silverman, Brian S.; Stern, Scott, 1969- (Advances in strategic management, 2017)
Despite recent advances in our understanding of how innovation and entrepreneurship impact the creation and appropriation of value, numerous questions remain unanswered. This volume draws together scholars working at the forefront of entrepreneurship-, strategy-, and innovation-related domains to explore these questions.